Performans hubungan antara faktor internal dan eksternal dengan kinerja penyuluh pertanian lapangan di Kabupaten Sorong Provinsi Papua Barat Daya - Sagrim, Meky (Cassowary, 2025)
ABSTRACT: Civil servant extension workers are given full duties, responsibilities, authorities and rights by authorized officials in organizational units within the scope of agriculture, animal husbandry, fisheries and forestry to carry out extension activities. Field agricultural extension workers have the main tasks and functions that must be carried out to achieve good performance. This study aims to evaluate the performance of field agricultural extension workers and what factors affect the performance of field agricultural extension workers in Sorong Regency. This research was conducted through interviews using questionnaires where sampling was carried out by census of 73 respondents of civil servant field agricultural extension workers consisting of 56 agricultural extension respondents and 17 livestock extension workers. Data analysis applied by tabulation with competency test techniques and then using PLS analysis (Partial Least Square). The results showed that the performance of field agricultural extension workers in Sorong Regency as a whole was in the medium category. PLS test results shows that there is a significant influence relationship between the performance of agricultural extension workers with internal factors consisting of age and education while external factors consist of information technology accessibility, appreciation and coaching and supervision. It can be concluded that the performance of agricultural extension workers in Sorong Regency overall still shows performance achievements that have not been fully reached.